Jenis dan Kelimpahan Fitoplankton di Waduk Sungai Paku Kecamatan Kampar Kiri Kabupaten Kampar Provinsi Riau - Yuris Fiestaria Naibaho; ’Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPhytoplankton is a primary producer organism in aquatic ecosystem and it supplies oxygen to the waters through photosynthesis process. A research aim to determine types and abundance of phytoplankton in the Sungai Paku Reservoir has been carried out on June-July 2019. Sampling taken at three stations, namely Station 1 (riverine zone), Station 2 (transition zone) and Station 3 (lacustrine zone), once/week. Parameters measured were temperature, transparency, depth, pH, DO, free CO2, nitrate (NO3) and phosphate (PO4). Result shown the types of phytoplankton found in the Sungai Paku Reservoir was 35 species that consist of 5 classes, namely Bacillariophyceae (5 species), Chlorophyceae (18 species), Cyanophyceae (7 species), Dinophyceae (2 species), and Euglenophyceae (3 species) and abudance of phytoplankton in the Sungai Paku Reservoir ranges from 78,336-182,016 cells/L. The water quality parameters were as follows: transparency 69.2-80.8 cm, temperature: 28.77-29.43 oC, pH 5, DO 3.53-4.42 mg/L, free CO2 10.56-11.44 mg/L, phosphate 0.077-0.111 mg/L, nitrate 0.085-0.109 mg/L. Based on phytoplankton abundance, Sungai Paku Reservoir can be categorized as mesotrophic. Keywords: Autotroph, Water Quality Parameters, Mesotrophic